2015
DOI: 10.1111/ejn.13047
|View full text |Cite
|
Sign up to set email alerts
|

Persistent alterations in active and passive electrical membrane properties of regenerated nerve fibers of man and mice

Abstract: Excitability of regenerated fibers remains impaired due to changes in both passive cable properties and alterations in the voltage-dependent membrane function. These abnormalities were studied by mathematical modeling in human regenerated nerves and experimental studies in mice. In three adult male patients with surgically repaired complete injuries of peripheral nerves of the arm 22 months-26 years prior to investigation, deviation of excitability measures was explained by a hyperpolarizing shift in the resti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…This matter, could in part be resolved, by performing nerve conduction velocity studies in both motor and sensory hindlimb nerves (i.e. tibial and sural nerve branches) since these are routinely performed in humans as well as in mice with suspected neuropathies [41]. …”
Section: Discussionmentioning
confidence: 99%
“…This matter, could in part be resolved, by performing nerve conduction velocity studies in both motor and sensory hindlimb nerves (i.e. tibial and sural nerve branches) since these are routinely performed in humans as well as in mice with suspected neuropathies [41]. …”
Section: Discussionmentioning
confidence: 99%
“…65 Alterations in passive cable properties (myelin thickness and internodal length) may also change membrane potential or ion channel conductances, for example, shorter internodes in regenerated nerve and an increased number of nodes provide a greater intra-axonal Na + load to drive the Na + /K + pump. 58 This concept is unlikely as latency and conduction velocities were maintained and mathematical modeling did not support this as the most plausible explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term studies of regenerated axons in a cat model demonstrated a tendency for depolarizing threshold electrotonus to return toward normal while abnormalities in hyperpolarizing threshold electrotonus persisted . Further exploration of this discrepancy suggested that the combination of structural shortening of internodal segments and overactivity of outwardly rectifying fast potassium currents may be the underlying cause …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the changes that were recorded may potentially reflect alterations in surviving as well as regenerated axons, and thus longitudinal studies will be required to definitively establish the exact contribution of each fiber type to the excitability changes noted in this study. Previous studies have shown that axonal excitability abnormalities in regenerating axons after Wallerian degeneration may persist for a prolonged period after the initial insult, 11,13 and these changes have been attributed to altered fiber diameter, shortened internodal length, altered resting membrane potential, and altered rectification properties. 14 Of note, there were no differences in excitability parameters between patients with greater vs. lower clinical severity of disease, as measured by the House-Brackmann score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation